ROLE OF COMPATIBLE POLLINIZER FOR COMMERCIAL OLIVE PRODUCTION IN POTHWAR, PAKISTAN. - A. Iqbal; A. Mahmood; M. A. Khan; T. Ahmad; M. Azam; M. I. N. Bhatti; A. A. Awan; I. A. Hafiz (Journal of Animal and Plant Sciences, 2020)
The final fruit yield is significantly correlated to fruit set which is directly dependent upon self-incompatibility (SI), pollination ability, extent of cross-compatibility among cultivars, and prevailing environmental conditions especially suitable temperature regimes during anthesis. Four Italian cultivars viz. Coratina, Frantoio, Ottobratica, and Leccino under the agro-climatic conditions of Pothwar (Pakistan) were included in these studies during the years of 2017 & 2018. Each variety exhibited different values for the initial fruit set, final fruit set, number of shotberries and extent of self-incompatibility index. The SI resulted through reciprocal crosses depicted that cv. Coratina (0.80), cv. Frantoio (0.67) and cv. Leccino (0.73) possessed partial self-incompatibility while cv. Ottobratica (0.43) was found completely self-incompatible in studied environmental conditions. Cross-compatibility results based on fruit set percentage indicated that the cultivars can efficiently pollinize other cultivars and set good fruit yield, however, the cultivars pairs Coratina/Frantoio was at top and pair of Ottobratica/ Leccino was at the bottom. Thus, the selection and plantation of suitable pollinizers in olive orchards is a prerequisite through which deficiency in fruit setting and attaining commercial yield in olive orchards could be achieved.
Keywords: olive; Pakistan; self-incompatibility index; pollinizer; cross-compatibility